Lloyd, Seton Howard Frederick (30.5.1902-7.1.1996) - Collon, Dominique
AfO 42/43 (1995/1996) 335-337 (G.R.H. Wright); Anatolian Archaeology Research Reports of the British Institute of Archaeology at Ankara 2 (1996) 3 (O.R. Gurney)